THE IMPACT AND POSSIBILITIES OF TRAINING IN IMPROVING CAREER MOTIVATION IN PUBLIC SECTOR: AN APPLIED STUDY: AL-FURAT AL-AWSAT UNIVERSITY - TECHNICAL INSTITUTE - DIWANIYAH - Huossein Mohamed Saad; Bushra Kadhim Abdulhussein (Galaxy International Interdisciplinary Research Journal, 2023)
The study aimed to know the effect of training workers in achieving the motivation of the career path, and the importance of the study stems from the fact that training workers and developing the career path are an important and necessary part of human resource management strategies, and they are also important topics for study and scientific research in the field of business administration and organizational psychology, The study followed the analytical descriptive approach, and the study population consisted of all employees working in the Middle Euphrates University - Diwaniyah Technical Institute - Iraq, whose number is 480 employees.